GENETIC POLYMORPHISM ANALYSIS OF FIVE VIETNAM NATIVE AC, CHOI, HO, H’MONG AND TRE CHICKEN BREEDS USING MICROSATELLITES - Thuý, Lê Thị (Vietnam Journal of Biotechnology, 2011)
Twenty microsatellite loci were used for genetic polymorphism analysis of five Vietnam native chicken populations. Blood unrelated samples of five native chicken breeds: Ac, Choi, H’mong, Ho and Tre (each with 40) were collected from Long An, Binh Dinh, Ha Giang, Bac Ninh and Ben Tre. For 20 microsatellites, total alleles in each breed was 102; 130; 124; 106, 130 and the mean number of alleles per locus was 5.1; 6.5; 6.2; 5.3; 6.5 for Ac, Choi, H’mong, Ho and Tre breeds respectively. The average number of allele/locus of total research individuals breeds was very high 8.4. The mean observed (Ho) and expected heterozygosity (He), were: 0.563 and 0.626 respectively. The average of inbreeding coefficient (Fis) and the average genetic variation (Fst) between breeds were 0.010; 0.032 respectively, Small Nei’s (1972) standard genetic distances ranging 0.033 to 0.108 were observed between 5 breeds. The results showed that genetic diversity of five chicken breed populations was high and five breeds belonged to three different groups, one including Tre, one including Ac and one including H’mong, Choi, and Ho chicken in which Choi chicken had a closer relationship to Ho than to the Hmong chicken.